If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+25/5=86/6
We move all terms to the left:
x+25/5-(86/6)=0
We add all the numbers together, and all the variables
x+25/5-(+86/6)=0
We add all the numbers together, and all the variables
x+5-(+86/6)=0
We get rid of parentheses
x+5-86/6=0
We multiply all the terms by the denominator
x*6-86+5*6=0
We add all the numbers together, and all the variables
x*6-56=0
Wy multiply elements
6x-56=0
We move all terms containing x to the left, all other terms to the right
6x=56
x=56/6
x=9+1/3
| 3x-1/3x-9=8(1/3x+6) | | 2(x+5)=-3x-5 | | 4(5x-4)-1=-37 | | 4(5x+4)=x-22 | | 9xx-3.2=6.8+8x | | (x–5)^2-72=9 | | ‘1.5(q-4)-2=4 | | 2q+12=40 | | x+0.21x=1999 | | (-8)^-3x=(-6)^-3 | | x=(-6)^-3/(-8)^-3 | | 5-t/3=6 | | 13-y=26× | | 7/8a=-43 | | 0.8x0.5=4 | | 11=35a+24 | | 3x+29=7x+11 | | x-(75/100*x)=600 | | x-75/100*x=600 | | F(a)=a²-6 | | 4(5x−2)=6(2x−4) | | -6x=-3/2 | | 2x=540-3x | | 540-2x=x | | 4c-3=11 | | -4/9=8/15x | | 6(x-1)+2(x-5)=28 | | 5m-7=8m+1 | | -7(3q+8)=-14 | | 9x-69=-6 | | a2=-5^2-1 | | P=x2-5x |